Performance Study of OCR (Over Current Relay) and GFR (Ground Fault Relay) Relays as Protection In 20 Kv Cubicles in Selayang GH PT. PLN UP2D North Sumatra - Apda Eriansyah; Parlin Siagian; Rahmaniar Rahmaniar (Jurnal Info Sains : Informatika dan Sains, 2026)
Power system protection is crucial for maintaining energy distribution reliability. This study aims to evaluate the performance of Over Current Relay (OCR) and Ground Fault Relay (GFR) as protection systems in 20 kV cubicles at Selayang Switching Station (GH) PT PLN UP2D North Sumatra. The research method used is descriptive quantitative with an engineering case study approach. Data were collected through field observations, short-circuit fault current calculations, and physical testing using the Omicron CMC 353 secondary current injection tool. The results show that the maximum short-circuit fault current of 14.4 kA is still below the circuit breaker's breaking capacity of 16 kA. The pick-up current settings on feeders SLY 05, SLY 06, and SLY 07 met the sensitivity criterion (1.2 x Imax), and the time coordination (grading margin) between protection devices was within the ideal range of 0.25 to 0.5 seconds. Validation through injection testing showed high accuracy with an average operating time deviation of less than 10% according to PLN standards. The conclusion of this study confirms that the protection system at GH Selayang operates efficiently, precisely, and reliably in securing network assets and ensuring the continuity of electricity supply.